An Evaluation of an eHealth Tool Designed to Improve College Students’ Label-Reading Skills and Feelings of Empowerment to Choose Healthful Foods - Miller, Lisa M. Soederberg; Sutter, Carolyn A.; Wilson, Machelle D.; Bergman, Jacqueline J.; Beckett, Laurel A.; Gibson, Tanja N. (Frontiers in Public Health, 2018)
Objective College students are at risk for poor dietary choices. New skills can empower individuals to adopt healthful behaviors, yet eHealth tools designed to develop food-choice skills, such as label-reading skills, are uncommon. We investigated the effects of web-based label-reading training on college students’ perceptions of healthful food-choice empowerment. Methods Students completed label-reading training in which they practiced selecting the more healthful food using nutrition labels. We examined improvements in label-reading accuracy (correct healthfulness decisions) and perceptions of empowerment, using a 6-item scale. Repeated measures ANOVAs and paired-samples t-tests were used to examine changes in accuracy and empowerment across the training session. Results In addition to increases in label-reading accuracy with training, we found increases in healthful food-choice empowerment scores. Specifically, the proportion of correct (i.e., more healthful) food choices increased across the three blocks of practice (p = 0.04) and food-choice empowerment scores were about 7.5% higher on average after training (p < 0.001). Conclusion and implications Label-reading training was associated with increased feelings of empowerment associated with making healthful food choices. Skill focused eHealth tools may offer an important avenue for motivating behavior change through skill development.